2022
DOI: 10.3390/ani12070823
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of Dietary Herbal Essential Oils in Aquaculture: A Review

Abstract: The aquaculture sector is one of the main activities contributing to food security for humanity around the globe. However, aquatic animals are susceptible to several farming stressors involved in deteriorated growth performance, reduced productivity, and eventually high mortality rates. In some countries still, antibiotics and chemotherapies are comprehensively applied to control biotic stressors. Aside from the apparent benefits, the continuous usage of antibiotics develops bacterial resistance, deteriorates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 165 publications
(220 reference statements)
2
28
0
3
Order By: Relevance
“…Histopathological findings revealed hyperplasia of melanomacrophage centers in spleen .This result came in parallel to the hematological and immunological results in the current study, confirming the improvement in the hematopoietic system and the innate immune response expressed by the up-regulation of TNF-α and IL-1β proving the role of essential oils as immunostimulants and disease resistance (Dawood et al, 2022).…”
Section: Panigrahisupporting
confidence: 89%
“…Histopathological findings revealed hyperplasia of melanomacrophage centers in spleen .This result came in parallel to the hematological and immunological results in the current study, confirming the improvement in the hematopoietic system and the innate immune response expressed by the up-regulation of TNF-α and IL-1β proving the role of essential oils as immunostimulants and disease resistance (Dawood et al, 2022).…”
Section: Panigrahisupporting
confidence: 89%
“…Te results also showed improved immune and antioxidative responses as well as high resistance to Aeromonas hydrophila infection in Nile tilapia. Te obtained results confrm the hypothesis of the necessity of adding herbal extracts to sustain the productivity of fnfsh species [52]. In the same line, Yu et al [21] reported that fenugreek seed extract enhanced the biochemical blood indices, antioxidative capacity, and immune response of blunt snout bream.…”
Section: Discussionsupporting
confidence: 72%
“…Medicinal plants and their extracts, bioactive functional constituents and essential oils have been succeeded in strengthening the immunity, antioxidant status and improving growth rates of several aquaculture fish (Ahmadifar et al, 2021;Dawood et al, 2021;Dawood et al, 2022) analysis of the compounds present in MOL (Figure 1 and Table 2)…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants and their extracts, bioactive functional constituents and essential oils have been succeeded in strengthening the immunity, antioxidant status and improving growth rates of several aquaculture fish (Ahmadifar et al, 2021; Dawood et al, 2021; Dawood et al, 2022). M. oleifera is well‐known to have numerous health advantages that have been accredited to its phytochemicals like flavonoids and phenolic compounds (Verma et al, 2009; Vongsak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%